Creation of Video Games as an Educational Strategy in Algorithms (Docentes 2.0 Journal, 2021)
Introducing students to the study of programming basics is not an easy task; it requires time, effort, and a particular focus on how it is learned and taught. Computer programming and especially the basic principles of this area are essential aspects. For this reason, the Autonomous University of Yucatán (UADY) created in the Tizimín Multidisciplinary Unit (UMT) the bachelor’s degree in Software Engineering (LIS), and it began to teach the subject of Algorithmic in the first semester of the career. Included research based on the Scratch programming language was in the Algorithmic issue to support understanding the basic structures studied in it. In this way, the student-organized in workgroups could create a video game to translate their knowledge. The inclusion of Scratch to Algorithm, hand in hand with the project-based learning methodology and the theory of constructionism, allowed the students to develop their video games. The mixed methodological approach was the research approach, and the sample consisted of all the students enrolled in Algorithmic in three semester periods. During this time, 24 video games were generated which met the objectives set, and the results obtained from the entire investigative process have been satisfactory.
Keywords: Videogames; scratch; algorithms